2019
DOI: 10.1080/09638288.2019.1626919
|View full text |Cite
|
Sign up to set email alerts
|

Activity limitations and participation restrictions in people with multiple sclerosis: a detailed 10-year perspective

Abstract: Aim: To conduct a detailed investigation into changes in activity limitations and participation restrictions over 10 years in people with mild, moderate and severe multiple sclerosis. Methods: This study was a 10-year longitudinal study of 264 people with multiple sclerosis living in Stockholm County, Sweden. Ten-year changes in personal and instrumental activities in daily living were assessed using the Katz Activities in Daily Living Index Extended and participation in social/lifestyle activities using the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 49 publications
3
10
0
2
Order By: Relevance
“…Work ability reflects the extent to which people can do their job satisfactorily, taking their job demands and their (physical and mental) health into account [6]. Having a chronic disease, associated with activity limitations, can lead to decreased mental and physical functioning [7][8][9], and therefore threatening work ability and working hours [10][11][12]. In comparison to healthy workers, workers with a chronic disease work fewer hours and more often parttime due to differences in fatigue and emotional exhaustion [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Work ability reflects the extent to which people can do their job satisfactorily, taking their job demands and their (physical and mental) health into account [6]. Having a chronic disease, associated with activity limitations, can lead to decreased mental and physical functioning [7][8][9], and therefore threatening work ability and working hours [10][11][12]. In comparison to healthy workers, workers with a chronic disease work fewer hours and more often parttime due to differences in fatigue and emotional exhaustion [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In a prospective cohort research, changes in activity limitation and participation over a period of 10 years were studied in a Swedish population of persons with MS. 17 Results indicated that people in the mild stages of MS showed restrictions in a few domains of participation, whereas the moderate group experienced restricted participation in domestic and outdoor activities and most of the individuals with severe MS showed restricted participation in all social/lifestyle activities. Over time, an increase in participation restrictions was present across all MS groups, but mostly in the moderate group.…”
Section: Participationmentioning
confidence: 92%
“…As time passes since a person is diagnosed with MS, impairment will eventually debut and increase. 6 , 19 A longitudinal study found that over a 10-year period, many persons with MS’s capacity to participate in activities and society decreased. 19 Although there is no cure for MS, studies have showed positive outcomes in the social participation of persons with MS attending multidisciplinary rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 19 A longitudinal study found that over a 10-year period, many persons with MS’s capacity to participate in activities and society decreased. 19 Although there is no cure for MS, studies have showed positive outcomes in the social participation of persons with MS attending multidisciplinary rehabilitation. 20 , 21 This scoping review seeks to contribute to clinical practice by highlighting the societal barriers and discrimination that persons with MS face.…”
Section: Introductionmentioning
confidence: 99%